Physically‐cross‐linked poly(vinyl alcohol) cell culture plate coatings facilitate preservation of cell–cell interactions, spheroid formation, and stemness. Issue 11 (13th April 2021) - Molyneaux, Kathleen; Wnek, Maria D.; Craig, Sonya E.L.; Vincent, Jason; Rucker, Imani; Wnek, Gary E.; Brady‐Kalnay, Susann M.
Abstract: We employed aqueous solutions of highly‐hydrolyzed (>99+%) poly(vinyl alcohol), PVA, to coat plastic dishes as a method to efficiently induce three‐dimensional (3D) culturing of cells. The coatings were prepared by simple evaporation of 3 wt/vol% solutions of PVA in water and require no additional processing steps after air drying under sterile conditions. The coating allows spheroids to form in solution. Spheroid formation is usually preferable to two‐dimensional (2D) culturing as it creates a more realistic ex vivo model of some human tissues and tumors. Using PVA‐coated cell culture plates, we demonstrated that we can grow reproducibly sized spheroids using several human glioma cell lines, including LN229, U87 MG, and Gli36, and the embryonic kidney cell line, 293T. Spheroids formed on PVA‐coated plates grow as well as on other commercially‐available, low‐attachment plates, and have excellent optical imaging properties. As spheroids, LN229 cells express markers of cancer stem cells. Finally, we confirmed that spheroids generated on PVA‐coated plates are sensitive to molecular perturbations, as increased expression of the cell adhesion molecule PTPμ significantly increased the size of spheroids. The PVA hydrogel layer is an effective tool for creating a more realistic ex vivo culture system than traditional 2D culture and can be used to generate cell spheroids for potential application in drug screening and personalized medicine for diseases such as cancer.